Nonlinear heading control of an autonomous underwater vehicle with internal actuators. (1st October 2016) - Li, Bo; Su, Tsung-Chow
Abstract: Designs of hybrid autonomous underwater vehicles (AUVs), which use internal actuators instead of control surfaces to steer, have emerged recently in the ocean engineering community. This paper focuses on the heading autopilot design for a REMUS AUV by using an internal moving mass. A nonlinear dynamical system is first derived which describes the horizontal-plane motion of the vehicle coupled with an internal moving mass. It is shown that a displacement of the internal mass in the sway direction can affect the flow of the dynamical system in phase space. Using displacement as the system input, a LQR controller is designed to stabilize the heading angle of the vehicle by taking advantage of the position and inertia of the internal moving mass. The linear controller cannot deal with large perturbations due to the constraints on the maximum displacement and movement speed of the internal moving mass. Consequently, a tunnel thruster is added to the design in order to address the problem. A nonlinear full-state feedback law is derived based on backstepping and Lyapunov redesign technique to control the displacement of the internal mass and the force exerted by the tunnel thruster. Simulation results demonstrate the effectiveness of the proposed design.